Upaya Peningkatan Pengetahuan untuk Mencegah Mengurangi Bullying Melalui Permainan Ular Tangga pada Siswa di SD Negeri 3 Wonorejo Karanganyar (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
Bullying is a social problem that still frequently occurs in elementary school settings and may negatively affect children’s psychological development. Improving knowledge from an early age is one of the preventive efforts to reduce bullying behavior. This study aimed to determine the effectiveness of the educational snakes and ladders game as a learning medium in improving students’ knowledge about bullying at SD Negeri 3 Wonorejo, Karanganyar. This study employed a pre-experimental one-group pretest-posttest design. The subjects were 23 fourth- and fifth-grade students. The instrument was a questionnaire assessing knowledge of bullying. The results showed an increase in the students’ average knowledge scores after the intervention using the Snakes and Ladders game. This medium was proven to deliver educational messages in an interesting, enjoyable, and effective way, while also encouraging positive interaction among students during the learning process. The educational snakes and ladders game can therefore be used as an alternative educational medium for bullying prevention in elementary schools.